Super duplex stainless steel flux-cored wire with high toughness and hydrogen resistance and preparation method
By adjusting the composition of the flux core powder and heating treatment in an inert gas atmosphere, a super duplex stainless steel flux core welding wire with high toughness and high hydrogen resistance is formed, which solves the problem that existing welding wires are prone to cracks and failures in hydrogen environments. .
Patent Information
- Application Number
- CN202411797624.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
Existing super duplex stainless steel flux-core welding wires are difficult to have high toughness and high hydrogen resistance at the same time, resulting in cracks and failures of welded joints in hydrogen environments.
By adjusting the composition of the powder of the medicine core, the content is Cr: 32.3%~35.8%, Ni: 1%~4%, Mo: 10%~14%, TiN: 0.5%~3%, Nb: 0.1%~1%, Mn: 2%~5%, Si: 0.5%~1.0%, and heated in an inert gas atmosphere to form a flux-core welding wire.
Improves the hydrogen resistance and strength of the welded joints, reduces the risk of hydrogen embrittlement, and is suitable for key structures and components in high-pressure hydrogen environments.
Smart Images

Figure CN119426844A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of welding materials, and in particular relates to a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance. The present invention also relates to a preparation method of the super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance. Background Art
[0002] In modern industry, super duplex stainless steel has been widely used in the fields of petroleum, natural gas, and chemical industry. The presence of hydrogen atoms in a hydrogen environment places higher requirements on the performance of welding materials. Since hydrogen is the element with the smallest relative atomic mass in the periodic table, it is easy to enter metal materials. When the hydrogen content in metal materials reaches a certain concentration, it will cause a series of irreversible hydrogen damage such as hydrogen blistering, hydrogen-induced cracks, and hydrides. Therefore, the problem of hydrogen embrittlement has always been a key issue restricting the use of high-strength steel. When there is an external load, hydrogen will be enriched at the defects through stress-induced hydrogen diffusion, causing the plasticity of the metal material to be significantly reduced, causing hydrogen lag cracks, and thus causing failure and cracking of the welded joints in industrial production, thereby causing various accidents and causing economic losses. Therefore, how to improve the hydrogen resistance of welded joints has become a major pain point in the industry.
[0003] Existing anti-hydrogen measures, such as alloying, introduce impurities to form hydrogen traps when producing hydrogen storage materials to capture hydrogen atoms and achieve hydrogen resistance. This requires precise control of the amount of refiner added and requires special production equipment. These shortcomings affect the performance of the material, resulting in a decrease in the strength, plasticity and other properties of the material. Heat treatment has high energy consumption, and a large amount of energy is required to heat and maintain the temperature during the production process. Heat treatment is difficult to achieve in the field, especially for large equipment and welded joints. These traditional anti-hydrogen measures have obvious shortcomings and cannot simultaneously meet the material's needs for high performance and high hydrogen resistance. Therefore, it is crucial to develop a welding material that can meet both the toughness requirements of the welded joint and its hydrogen resistance. Summary of the invention
[0004] The purpose of the present invention is to provide a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance, which solves the problem that the super duplex stainless steel flux-cored welding wire in the prior art is difficult to have both high toughness and high hydrogen resistance, and greatly improves the strength of the joint after welding.
[0005] Another object of the present invention is to provide a method for preparing a super duplex stainless steel flux-cored welding wire having high toughness and hydrogen resistance.
[0006] The first technical solution adopted by the present invention is a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance, comprising a weld skin and a flux-cored powder filled in the weld skin, wherein the flux-cored powder is composed of the following components by mass percentage: Cr: 32.3%~35.8%, Ni: 1%~4%, Mo: 10%~14%, TiN: 0.5%~3%, Nb: 0.1%~1%, Mn: 2%~5%, Si: 0.5%~1.0%, and the rest is iron powder, and the total content of the above components is 100%.
[0007] The first technical solution of the present invention is also characterized in that: The weld skin is 0Cr18Ni9 austenitic stainless steel strip.
[0008] The filling amount of flux core powder in the welding skin is 18%~23%.
[0009] The second technical solution adopted by the present invention is a method for preparing a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance, which specifically comprises the following steps: Step 1, weigh the following raw materials respectively by mass percentage: Cr: 32.3%~35.8%, Ni: 1%~4%, Mo: 10%~14%, TiN: 0.5%~3%, Nb: 0.1%~1%, Mn: 2%~5%, Si: 0.7%~3.2%, and the rest is iron powder. The total content of the above raw materials is 100%; Step 2, heating and keeping the raw material powder in an inert gas atmosphere to remove moisture and obtain a core powder; Step 3, select the outer skin and place it on the unwinding machine of the welding wire forming machine, and roll the outer skin into a U-shaped groove through the groove pressing of the forming machine; Step 4, after cooling the core powder in step 2 to room temperature, fill it into the U-shaped groove, pass through the closed forming roller, and finally form the cored welding wire through the step-by-step diameter reduction method.
[0010] The second technical solution of the present invention is also characterized in that: The particle size of each raw material in step 1 is 90 mesh to 110 mesh.
[0011] In step 2, the inert gas is argon with a purity of 99.999%.
[0012] In step 2, the heating temperature is 150°C to 200°C, and the insulation time is 2h to 2.5h.
[0013] The outer skin is 0Cr18Ni9 austenitic stainless steel strip, the width of the outer skin is 6mm~8mm, and the thickness is 0.3mm~0.4mm.
[0014] The filling amount of the core powder filled into the U-shaped groove in step 4 is 18% to 23%.
[0015] The beneficial effects of the present invention are: The preparation method of the super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance of the present invention reduces the risk of hydrogen embrittlement by adding chromium and molybdenum to improve corrosion resistance and increase hydrogen traps; improves the corrosion resistance of the welding wire by adding niobium (Nb) elements, thereby improving welding performance; and improves the mechanical properties of the weld after welding, suppresses pores in the welding process, and improves the strength of the weld joint by adding Mn elements; as a whole, the hydrogen-resistant material performs well in high strength, high toughness and high corrosion resistance, and is widely used in key structures and components in high-pressure hydrogen environments.
[0016] At the same time, the super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance of the present invention has a short preparation cycle and high production efficiency. The performance can be improved by adjusting the flux core composition and proportion. At the same time, the flux-cored welding wire production is pollution-free and the welding process has high cladding efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the microtube of the flux-cored welding wire prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0019] Example 1 The invention discloses a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance, comprising a welding skin and a flux-cored powder filled in the welding skin, wherein the flux-cored powder is composed of the following components by mass percentage: Cr: 32.3%-35.8%, Ni: 1%-4%, Mo: 10%-14%, TiN: 0.5%-3%, Nb: 0.1%-1%, Mn: 2%-5%, Si: 0.5%-1.0%, and the rest is iron powder, and the total content of the above components is 100%.
[0020] Furthermore, the weld skin is 0Cr18Ni9 austenitic stainless steel strip.
[0021] Furthermore, the filling amount of the flux core powder in the welding skin is 18%~23%.
[0022] The super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance of the present invention has a short preparation cycle and high production efficiency. The performance can be improved by adjusting the flux core composition and proportion. At the same time, the flux-cored welding wire is pollution-free in production and has high cladding efficiency in the welding process.
[0023] Specifically, chromium (Cr) is an important element to improve the corrosion resistance of materials. It reacts with oxygen to form a dense chromium oxide film. This oxide film attached to the surface effectively prevents the penetration of hydrogen. Chromium not only forms a solid solution in steel, which improves the hardness and strength of the material, but also increases the hydrogen traps in the material, so that hydrogen will not diffuse and aggregate in the material, greatly reducing the risk of hydrogen embrittlement.
[0024] Molybdenum (Mo) element also promotes the formation of oxide film, thereby improving the corrosion resistance of the material. Cobalt not only forms a solid solution in steel, but also improves the hardness and strength of the material by refining the grains. In addition, chromium can increase the hydrogen traps of the material, so that hydrogen will not diffuse and aggregate in the material, greatly reducing the risk of hydrogen embrittlement.
[0025] The main effects of adding Ni element in the present invention include improving the corrosion resistance, thermal cracking resistance, strength and toughness of the welded joint. Specifically: Improve corrosion resistance: Ni element can significantly improve the corrosion resistance of the welded joint, especially in harsh environments such as chemical corrosion and seawater corrosion, the welded joint has better corrosion resistance. Improve thermal cracking resistance: During the welding process, thermal cracks are prone to occur in the welded joint during heating and cooling. Ni element can effectively inhibit and reduce the occurrence of thermal cracking, thereby improving the thermal cracking resistance of the welded joint. Improve strength and toughness: The addition of Ni element can make the welded joint have a certain strength and toughness, thereby increasing the service life and stability of the welded joint.
[0026] The TiN selected in the present invention has a NaCl type crystal structure, and has a small misalignment with ferrite, which promotes heterogeneous nucleation of ferrite and refines the ferrite grain boundaries. The refinement of ferrite provides a large number of grain boundaries for the formation of GBA, so austenite is preferentially formed in the form of GBA, and the amount of austenite in the grain is reduced. (More supercooling is required).
[0027] The main effects of adding niobium (Nb) element in the present invention include improving corrosion resistance and improving welding performance. Different contents of ferroniobium and ferrovanadium (3.2 wt.%, 6 wt.%, 10 wt.%) were added to 1Cr13 martensitic stainless steel for surfacing test. The results showed that with the increase of ferroniobium and ferrovanadium content in flux-cored welding wire, the number of precipitated phases in the surfacing deposited metal gradually increased. These precipitated phases are carbonitrides containing Nb and V, which can effectively inhibit the formation of Cr-rich precipitated phases and increase the effective Cr content in the matrix. A large number of evenly distributed precipitated phases are conducive to corrosion from multiple locations, promoting uniform corrosion of the surfacing deposited metal, thereby improving its corrosion resistance.
[0028] The main effects of adding manganese (Mn) elements in the present invention include improving the mechanical properties of the weld: Manganese can improve the hardness and strength of the weld, thereby enhancing the mechanical properties of the weld joint. When the manganese content is between 0.6% and 1.8%, the weld metal has higher strength and toughness. Improving the toughness of the weld joint: Manganese has a significant effect on the toughness of the weld metal. When the manganese content is between 0.6% and 1.8%, the weld metal has higher strength and toughness.
[0029] The main functions of adding silicon (Si) element in the present invention include deoxidation, preventing pores from forming, and optimizing weld microstructure. Silicon is the most commonly used deoxidizing element in welding wire. It can prevent iron from combining with oxygen and reduce FeO in the molten pool. However, when silicon is used alone for deoxidation, the generated SiO2 has a high melting point (about 1710°C) and the particles of the product are small and difficult to float out of the molten pool, which easily leads to slag inclusion in the weld metal.
[0030] Example 2 The method for preparing a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance of the present invention specifically comprises the following steps: Step 1, weigh the following raw materials respectively by mass percentage: Cr: 32.3%~35.8%, Ni: 1%~4%, Mo: 10%~14%, TiN: 0.5%~3%, Nb: 0.1%~1%, Mn: 2%~5%, Si: 0.7%~3.2%, and the rest is iron powder. The total content of the above raw materials is 100%; Furthermore, the particle size of each raw material is 90 mesh to 110 mesh.
[0031] Step 2, heating and keeping the raw material powder in an inert gas atmosphere to remove moisture and obtain a core powder; Furthermore, in step 2, the inert gas is argon with a purity of 99.999%.
[0032] Furthermore, in step 2, the heating temperature is 150° C. to 200° C., and the insulation time is 2 h to 2.5 h.
[0033] Step 3, select the outer skin and place it on the unwinding machine of the welding wire forming machine, and roll the outer skin into a U-shaped groove through the groove pressing of the forming machine; Furthermore, the outer skin is a 0Cr18Ni9 austenitic stainless steel strip, the width of the outer skin is 6mm~8mm, and the thickness is 0.3mm~0.4mm.
[0034] Step 4, after cooling the core powder in step 2 to room temperature, fill it into the U-shaped groove, pass through the closed forming roller, and finally form the cored welding wire through the step-by-step diameter reduction method.
[0035] Furthermore, the filling amount of the core powder filled into the U-shaped groove in step 4 is 18% to 23%.
[0036] The prepared flux-cored welding wire is wiped of oil stains with alcohol cotton cloth, and is sealed and packaged in a tray. The prepared flux-cored welding wire is loaded into a fully automatic welding robot, and the prepared flux-cored welding wire is surfacing-welded on a 42Cr substrate using a MIG welding method.
[0037] The preparation method of the super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance of the present invention, through the comprehensive application of various chemical components, makes the hydrogen-resistant material perform well in high strength, high toughness and high corrosion resistance, and is widely used in key structures and components in high-pressure hydrogen environments.
[0038] Example 3 Step 1: Weigh the following raw materials according to mass percentage: Cr: 32.8%, Ni: 2.97%, Mo: 10%, TiN: 1.0%, Nb: 0.1%, Mn: 5%, Si: 0.5%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%.
[0039] Step 2, heating and keeping the raw material powder weighed in step 1 in an inert gas atmosphere to remove moisture and obtain a core powder; In step 2, the heating temperature is 150°C to 200°C, and the insulation time is 2h to 2.5h.
[0040] Step 3, placing the outer skin on the unwinding machine of the welding wire forming machine, and rolling the outer skin into a U-shaped groove through the pressing groove of the forming machine; Step 4, the flux-cored powder obtained in step 2 is kept warm and then cooled to room temperature with the furnace, and then the powder is filled into a U-shaped groove with a filling amount of 20%, and a 1.9 mm welding wire is made after passing through a closed forming roller, and finally a 1.20 mm metal-type flux-cored welding wire is made through a step-by-step diameter reduction method.
[0041] Wipe the oil stains on the flux-cored welding wire with an alcohol cotton cloth, load the prepared flux-cored welding wire into a fully automatic welding robot, and use the MIG welding method to overlay the coating on the 42Cr substrate. The arc is stable during welding, the forming is beautiful, and there are no defects such as cracks and pores. The obtained hydrogen-resistant coating has a tensile strength of 791.8MPa, an elongation of 33.1%, a hydrogen embrittlement sensitivity of 10.98%, and excellent hydrogen resistance, which meets the use requirements.
[0042] Example 4 Step 1: Weigh the following raw materials according to mass percentage: Cr: 35.8%, Ni: 1.97%, Mo: 12.28%, TiN: 0.5%, Nb: 0.5%, Mn: 2%, Si: 0.5%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%.
[0043] Step 2, heating and keeping the raw material powder weighed in step 1 in an inert gas atmosphere to remove moisture and obtain a core powder; In step 2, the heating temperature is 150°C to 200°C, and the insulation time is 2h to 2.5h.
[0044] Step 3, placing the outer skin on the unwinding machine of the welding wire forming machine, and rolling the outer skin into a U-shaped groove through the pressing groove of the forming machine; Step 4, the flux-cored powder obtained in step 2 is kept warm and then cooled to room temperature with the furnace, and then the powder is filled into a U-shaped groove with a filling amount of 23%. After passing through a closed forming roller, a 1.9 mm welding wire is made, and a 1.20 mm metal-type flux-cored welding wire is finally made through a step-by-step diameter reduction method.
[0045] Wipe the oil stains on the flux-cored welding wire with an alcohol cotton cloth, load the prepared flux-cored welding wire into a fully automatic welding robot, and use the MIG welding method to overlay the coating on the 42Cr substrate. The arc is stable during welding, the forming is beautiful, and there are no defects such as cracks and pores. The obtained hydrogen-resistant coating has a tensile strength of 803.1MPa, an elongation of 35.6%, and a hydrogen embrittlement sensitivity of 11.42%. It has excellent hydrogen resistance and meets the use requirements.
[0046] Example 5 Step 1: Weigh the following raw materials according to mass percentage: Cr: 32.3%, Ni: 1%, Mo: 14%, TiN: 3%, Nb: 1%, Mn: 4.2%, Si: 1%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%.
[0047] Step 2, heating and keeping the raw material powder weighed in step 1 in an inert gas atmosphere to remove moisture and obtain a core powder; In step 2, the heating temperature is 150°C to 200°C, and the insulation time is 2h to 2.5h.
[0048] Step 3, placing the outer skin on the unwinding machine of the welding wire forming machine, and rolling the outer skin into a U-shaped groove through the pressing groove of the forming machine; Step 4, the flux-cored powder obtained in step 2 is kept warm and then cooled to room temperature with the furnace, and then the powder is filled into a U-shaped groove with a filling amount of 18%, and a 1.9 mm welding wire is made after passing through a closed forming roller, and finally a 1.20 mm metal-type flux-cored welding wire is made through a step-by-step diameter reduction method.
[0049] Wipe the oil stains on the flux-cored welding wire with an alcohol cotton cloth, load the prepared flux-cored welding wire into a fully automatic welding robot, and use the MIG welding method to overlay the coating on the 42Cr substrate. The arc is stable during welding, the forming is beautiful, and there are no defects such as cracks and pores. The obtained hydrogen-resistant coating has a tensile strength of 789.9MPa, an elongation of 31.4%, a hydrogen embrittlement sensitivity of 8.21%, and excellent hydrogen resistance, which meets the use requirements.
[0050] Example 6 Step 1: Weigh the following raw materials according to mass percentage: Cr: 33.8%, Ni: 4%, Mo: 12.28%, TiN: 1.0%, Nb: 0.5%, Mn: 2.2%, Si: 1.0%, and the rest is iron powder. The sum of the mass percentages of the above components is 100%.
[0051] Step 2, heating and keeping the raw material powder weighed in step 1 in an inert gas atmosphere to remove moisture and obtain a core powder; In step 2, the heating temperature is 150°C to 200°C, and the insulation time is 2h to 2.5h.
[0052] Step 3, placing the outer skin on the unwinding machine of the welding wire forming machine, and rolling the outer skin into a U-shaped groove through the pressing groove of the forming machine; Step 4, the flux-cored powder obtained in step 2 is kept warm and then cooled to room temperature with the furnace, and then the powder is filled into a U-shaped groove with a filling amount of 19%, and a 1.9 mm welding wire is made after a closed forming roller, and a 1.20 mm metal-type flux-cored welding wire is finally made by a step-by-step reduction method; Wipe the oil stains on the flux-cored welding wire with an alcohol cotton cloth, load the prepared flux-cored welding wire into a fully automatic welding robot, and use the MIG welding method to overlay the coating on the 42Cr substrate. The arc is stable during welding, the forming is beautiful, and there are no defects such as cracks and pores. The obtained hydrogen-resistant coating has a tensile strength of 843.5MPa, an elongation of 37.5%, a hydrogen embrittlement sensitivity of 6.03%, and excellent hydrogen resistance.
[0053] like Figure 1 As shown in the figure, the microstructure of the weld after welding in this embodiment is austenite + ferrite. It can be clearly seen from the figure that the austenite structure provides the material with higher strength, while the lower content of ferrite and the uniform austenite structure provide the material with good toughness. By adding elements such as TiN and Nb, nucleation points are provided, the columnar grains of duplex stainless steel in traditional surfacing are changed, and the corrosion resistance and hydrogen resistance of duplex stainless steel are enhanced.
[0054] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.
[0055] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0056] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance, comprising a welding skin and a flux-cored powder filled in the welding skin, characterized in that: The core powder is composed of the following components by mass percentage: Cr: 32.3%~35.8%, Ni: 1%~4%, Mo: 10%~14%, TiN: 0.5%~3%, Nb: 0.1%~1%, Mn: 2%~5%, Si: 0.5%~1.0%, and the rest is iron powder, and the total content of the above components is 100%.
2. The super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance according to claim 1, characterized in that: The welding skin is 0Cr18Ni9 austenitic stainless steel strip.
3. The super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance according to claim 1, characterized in that: The filling amount of the flux core powder in the welding skin is 18% to 23%.
4. A method for preparing a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance, comprising the following steps: Step 1, weigh the following raw materials respectively by mass percentage: Cr: 32.3%~35.8%, Ni: 1%~4%, Mo: 10%~14%, TiN: 0.5%~3%, Nb: 0.1%~1%, Mn: 2%~5%, Si: 0.7%~3.2%, and the rest is iron powder. The total content of the above raw materials is 100%; Step 2, heating and keeping the raw material powder in an inert gas atmosphere to remove moisture and obtain a core powder; Step 3, select the outer skin and place it on the unwinding machine of the welding wire forming machine, and roll the outer skin into a U-shaped groove through the groove pressing of the forming machine; Step 4, after cooling the core powder in step 2 to room temperature, fill it into the U-shaped groove, pass through the closed forming roller, and finally form the cored welding wire through the step-by-step diameter reduction method.
5. The method for preparing a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance according to claim 4, characterized in that: The particle size of each raw material in step 1 is 90 mesh to 110 mesh.
6. The method for preparing a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance according to claim 4, characterized in that: The inert gas in step 2 is argon with a purity of 99.999%.
7. The method for preparing a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance according to claim 4, characterized in that: In step 2, the heating temperature is 150° C. to 200° C., and the insulation time is 2 h to 2.5 h.
8. The method for preparing a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance according to claim 4, characterized in that: The outer skin is a 0Cr18Ni9 austenitic stainless steel strip, the width of the outer skin is 6mm~8mm, and the thickness is 0.3mm~0.4mm.
9. The method for preparing a super duplex stainless steel flux-cored welding wire with high toughness and hydrogen resistance according to claim 4, characterized in that: The filling amount of the core powder filled into the U-shaped groove in step 4 is 18% to 23%.
Citation Information
Patent Citations
A flux-cored wire for soldering diphasic stainless steel
CN101157160A
Metal flux-cored wire for 2205 duplex stainless steel and preparing method thereof
CN104668819A
Metal flux-cored wire for 2505 duplex stainless steel, and preparation method of metal flux-cored wire
CN104690445A
Super duplex stainless steel flux-cored wire
CN106695156A
Flux-cored wire for maritime work pipe structural member additive material and preparation and use method of flux-cored wire
CN116652449A